Antimicrobial use in Japanese hospitals: results from point prevalence survey in Aichi, 2020 - Hiroshi Morioka; Tetsuya Yagi (Journal of Global Antimicrobial Resistance)
AIM: This study aimed to provide an overview of antimicrobial use (AMU) for inpatient in Japanese hospitals. BACKGROUND: To promote effective antimicrobial stewardship, epidemiological data of AMU are essential. However, comprehensive information on AMUs in Japanese hospitals is limited. METHODS: A multicentre point-prevalence survey (PPS) was conducted in 27 hospitals across the Aichi Prefecture between February and July 2020. This study encompassed diverse hospital types, including community, university, and specialized hospitals. Information on the demographic data of the patients, underlying conditions, treated infections, details of AMU (indication: for treatment of community-acquired infections [CAIs]/healthcare-associated infections [HAIs], surgical antimicrobial prophylaxis [SAP], medical prophylaxis [MP]). RESULTS: A total of 10,199 patients were included in this study. A total of 3,738 antimicrobials were prescribed to 3,024 patients (29.6 %, 95% confidence interval [CI]: 28.8-30.5). Of 40.4% of antimicrobials were prescribed for treatment of CAIs, 21.8% were for treatment of HAIs, 17.1% were for MP and 19.9% were for SAP. Prevalence of SAP over 2 days was 31.2% in total. Cefazolin (450), ceftriazone (343), and trimethoprim-sulfamethoxazole (TMP-SMX, 327) are the top three prescribed antimicrobial. Number of antimicrobials per 1,000 patients were highest in extra-large hospitals [472.4], and lowest in small hospitals [263.5]. Ceftriaxone and meropenem was most prescribed antimicrobials for CAI and HAI, respectively. CONCLUSIONS: This study highlights extensive AMU in a region in Japan, showing variation linked to hospital size, frequent prescriptions of broad-spectrum antimicrobials for HAI, high prescription rate of TMP-SMX as medical prophylaxis and prolonged SAP.